If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -8x + 4 = x + -9 + 13 Reorder the terms: 4 + 2x + -8x = x + -9 + 13 Combine like terms: 2x + -8x = -6x 4 + -6x = x + -9 + 13 Reorder the terms: 4 + -6x = -9 + 13 + x Combine like terms: -9 + 13 = 4 4 + -6x = 4 + x Add '-4' to each side of the equation. 4 + -4 + -6x = 4 + -4 + x Combine like terms: 4 + -4 = 0 0 + -6x = 4 + -4 + x -6x = 4 + -4 + x Combine like terms: 4 + -4 = 0 -6x = 0 + x -6x = x Solving -6x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -6x + -1x = x + -1x Combine like terms: -6x + -1x = -7x -7x = x + -1x Combine like terms: x + -1x = 0 -7x = 0 Divide each side by '-7'. x = 0 Simplifying x = 0
| 3x-14=3x-14 | | 1.1x+8=0.5x+20 | | 1.1x+8=0.5x+29 | | (20-2x)x=90 | | 5227.50=5100(1+.025r) | | y=9.5+100 | | y=-0.62+0.0005x | | y=-0.62+0.0005211x | | y=0.0005211x+-0.62 | | 2c+4+3c=-16 | | 2x^2+1=2x+12 | | 4y-5x=40 | | .6x+1.9x=5 | | .6x+1.9=5 | | 2x^2+43x-2730=0 | | a+5=3 | | 7-6(3-8x)=0 | | x^2-14x+36= | | log(100)=10 | | ?10x+1+7x=37 | | ?10x+1+7x=32 | | ?10x+1+7x= | | ?10x+1+7x=37 | | log(x+5)-log(1-5x)=0 | | .50(x-6)+1=2(x-10)-3 | | 6x+4+8x+18+(180-20x+4)=180 | | 10y-x= | | 3w-10=50 | | log(x+5)=log(1-5x) | | 16n^2-24n+9= | | 4x-(6x-4)= | | 2x-4(x-1)= |